EFFICACY OF THE Β-TRICALCIUM PHOSPHATE IN THE STABILITY OF IMMEDIATE IMPLANT PLACEMENT- AN ORIGINAL RESEARCH - Gupta, Dr. Rajat; Gupta, Prabhakar; kumar, Sachin; Gupta, Tanu; Rawat, Siddhant; Singh, Priyanka (International Journal of Psychosocial Rehabilitation, 2020)
INTRODUCTION: The long term prognostic, functional and aesthetic success of the conventional noninvasive and osseointegrated dental prosthesis depends on the presence of sufficient volume of healthy jaw bone.AIM: To evaluate the efficacy of the β-tricalcium phosphate (β-TCP) in the stability of immediate implant placement in mandibular first molar cases in twelve weeks period using radiographic aids.MATERIAL & METHOD Ten patient of 20-55yrs of age meeting the criteria for the study and reporting to oral and maxillofacial surgery OPD of Subharti Dental College with un-restorable mandibular first molar were included in this study.RESULT: The mean densities for coronal buccal and lingual side, sagittal mesial and distal side, axial anterior, posterior, mesial and distal side were, 436.5 ± 374.7 & 381.2 ± 375.4 (p=0.006 & 0.004), 459 ± 493.7& 490 ± 508.4 (p= 0.020 & 0.018), 639.4 ± 567, 381.8 ± 658.3, 198.2 ± 329.2 & 274.4 ± 765.1(p= 0.008,0.115, 0.10& 0.30) respectively. The mean crestal bone loss on mesial and distal side were 0.60mm with SD of ± 0.6mm (p=0.02) and 0.4mm with SD of ±0.3mm (p=0.02) respectively.CONCLUSION: β-TCP doesn’t seem to be an ideal and highly beneficial bone filler around immediate implant placement, due to delayed osteoconduction and integration, poor handling and condensing property.